METHODS OF CONTENTS CURATOR (Journal of Information Technologies in Education (ITE), 2014)
Content curated - a new activity (started in 2008) qualified network users with process large amounts of information to represent her social network users. To prepare content curators developed 7 weeks distance course, which examines the functions, methods and tools curator.Courses showed a significant relationship success learning on the availability of advanced personal learning environment and the ability to process and analyze information.
Keywords: content curator; social services; methods; distance course